A Practical Guide to the E-Mail Interview - Hunt, Nigel; McHale, Sue (Qualitative health research, 2007)
The e-mail interview is a novel technique that has a number of advantages over traditional interviewing, but there are also some disadvantages. In this methodological article, the authors review the issues surrounding the use of the e-mail interview, providing a concrete example of its use, that of interviewing people with alopecia areata regarding psychological issues associated with the disorder. The authors show in the article that the e-mail interview is an effective interview technique but that users must take account of a number of sensitive issues, and there are a number of serious disadvantages that limit its use to specific areas. The e-mail interview cannot be used simply as a cheap alternative to face-to-face interviews in all circumstances.